Spatio-temporal evolution and driving mechanisms of landscape in the Yellow River Basin from 1985 to 2020 - Guo, Chao-fan; Zhao, Dongliang; Feng, Mei-fang (Frontiers in Ecology and Evolution, 2025)
IntroductionUnderstanding the landscape evolution and driving mechanisms in the Yellow River Basin (YRB) is crucial for safeguarding the ecological environment and promoting high-quality development in the region.MethodsThe analysis of spatio-temporal evolution characteristics of land use/land cover (LULC) and landscape pattern (LP) in the YRB employed transfer matrix and landscape pattern index models. Furthermore, a random forest regression method was utilized to investigate the driving mechanism behind landscape evolution.ResultsBased on our research findings, it is evident that significant changes have occurred in LULC, which have had profound implications for regional landscape patterns. The evolution of these patterns can be categorized into distinct stages. Between 1985 and 2010, there was a noticeable increase in clustering and interconnectedness, while between 2010 and 2020, this trend shifted. Grassland transformation primarily influenced landscape pattern evolution, whereas other LULC classifications had relatively limited effects on overall landscape integrity, diversity, and connectivity. Changes in grassland predominantly occurred at the outskirts of established grassland regions, while alterations in other LULC classifications were more sporadic due to human activities exerting influence.DiscussionLandscape evolution is synthetically influenced by both social and natural factors. Local changes are driven by social factors, while long-term gradual changes are primarily shaped by natural factors. Over the past three decades, social factors have played a significant role in shaping YRB’s landscapes.